Blood Pressure Responses to Renal Denervation Precede and Are Independent of the Sympathetic and Baroreflex Effects. Issue 6 (June 2015) - Grassi, Guido; Seravalle, Gino; Brambilla, Gianmaria; Trabattoni, Daniela; Cuspidi, Cesare; Corso, Rocco; Pieruzzi, Federico; Genovesi, Simonetta; Stella, Andrea; Facchetti, Rita; Spaziani, Domenico; Bartorelli, Antonio; et al.
<x xml:space="preserve">Abstract</x> It is still largely unknown whether the neuroadrenergic responses to renal denervation (RD) are involved in its blood pressure (BP)–lowering effects and represent predictors of the BP responses to RD. In 15 treated true resistant hypertensives, we measured before and 15 days, 1, 3, and 6 months after RD clinic, ambulatory and beat-to-beat BP. Measurements included muscle sympathetic nerve traffic (MSNA), spontaneous baroreflex–MSNA sensitivity, and various humoral and metabolic variables. Twelve treated hypertensives served as controls. BP, which was unaffected 15 days after RD, showed a significant decrease during the remaining follow-up period. MSNA and baroreflex did not change at 15-day and 1-month follow-up and showed, respectively, a decrease and a specular increase at 3 and 6 months after RD. No relationship, however, was detected between baseline MSNA and baroreflex, MSNA changes and BP changes. At the 6-month follow-up, the MSNA reduction was similar for magnitude in patients displaying a BP reduction greater or lower the median value. Similarly, the BP reduction detected 6 months after RD was similar in patients displaying a MSNA reduction greater or lower median value. No significant BP and MSNA changes were detected in the control group. Thus, the BP reduction associated with RD seems to precede the MSNA changes and not to display a temporal, qualitative, and quantitative relationship with the MSNA and baroreflex effects. Given the small sample size of the present study further investigations are warranted to confirm the present findings.